Synthesis, Structure, and Catalytic Activity of Bimetallic Rhodium Complexes in the Hydroformylation and Allylic Oxidation of Alkenes - Mkhize, Sinethemba (Department of Chemistry, 2023)
Four N,N'-bridging diphenylformamidine (dpf) ligands L1 – L4 were synthesised and characterised to ascertain purity. These known ligands were further reacted with the dimeric rhodium precursor [RhCl(COD)]2 producing a series of diphenylformamidinato-Rh(I) bimetallic complexes C1 – C4. The same ligands were also reacted with either the dirhodium trifluorotetraacetate [Rh2(TfOAc)4] or the traditional acetate [Rh2(OAc)4] dimers. Thes reactions yield a series of diphenylformamidinato-Rh(II) homoleptic bimetallic complexes C5 – C7 of the type [Rh2(R-dpf)4] (where R = H, CH3 or F) as well as the novel mixed ligand heteroleptic dirhodium complexes C8 – C11 of the type [Rh2(R-dpf)x(OAc)4-x] with x = 2 or 3 (where R = H, CH3 or F), respectively (Figure 1). The complexes were fully characterised using various spectroscopic and analytical techniques inclusive of the melting points, 1H NMR, 13C NMR, 19F NMR and FT-IR spectroscopy as well as high resolution mass spectrometry. Furthermore, UV-visible spectroscopy and cyclic voltammetry were carried out in various coordinating and none or poorly coordinating solvents to elucidate the absorption spectroscopy and electrochemical properties of the complexes. The Rh(I) bimetallic complexes C1 – C4 were evaluated as possible catalyst precursors in the hydroformylation of 1-octene, optimized at 85 oC and 30 bar of syngas (1:1 H2/CO). Facile and quantitative conversions were obtained within 4 hours under these conditions. All complexes have near quantitative conversion, with complete conversion for complex C4 (R = CF3). There is equal amount of both nonanal and branched aldehydes with C4, indicating the rate of isomerisation is equal to the rate of aldehyde formation from the iso-octenes. Homoleptic (C5 – C7) and mixed ligand heteroleptic (C8 – C11) dirhodium complexes were evaluated as potential catalysts towards the allylic oxidation of cyclohexene. At 0.1 mol% catalyst loading and 3 eq. of TBHP, a near quantitative substrate conversion was observed in the presence of a coordinating solvent, acetonitrile at 82 oC. Under such conditions, the heteroleptic complexes C8 – C11 demonstrate superior catalytic activity compared to the homoleptic complexes C5 – C7. The desired 2-cyclohexen-1-one is the dominant product over the 2-cyclohexen-1-ol and cyclohexene oxide which are also produced in this catalytic reaction.